2014
DOI: 10.1038/nrrheum.2014.85
|View full text |Cite
|
Sign up to set email alerts
|

The eye: a window of opportunity in rheumatoid arthritis?

Abstract: Rheumatoid arthritis (RA), the most common autoimmune disorder associated with dry eye syndrome, is also associated with sight-threatening ocular diseases such as peripheral ulcerative keratitis, scleritis and corneal melts. Tissue damage on the ocular surface of patients with RA is autoimmune-mediated. Findings from patients with dry eye have implicated defects in innate immunity (Toll-like receptors, S100A and resident antigen-presenting cells), cytokines, chemokines and T helper (TH)-cell subsets (including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 81 publications
0
41
0
Order By: Relevance
“…Tear film osmolarity also correlates with dry eye activity. Tong et al found in a recent study that tear film osmolarity correlated with the dry eye severity score 8. All this suggests that more research is needed on the markers of ocular surface in RA.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Tear film osmolarity also correlates with dry eye activity. Tong et al found in a recent study that tear film osmolarity correlated with the dry eye severity score 8. All this suggests that more research is needed on the markers of ocular surface in RA.…”
Section: Discussionmentioning
confidence: 97%
“…All this suggests that more research is needed on the markers of ocular surface in RA. Tong et al studied the immune factors that lead to dry eye and correlated them with systemic disease which could lead to potential treatment targets in the future showing the importance of conducting further studies on the ocular surface in RA patients 8. Villani et al studied the effect of immunosuppression on the ocular surface via confocal microscopy and cytokines level and found that immunosuppression modified the ocular surface pathology in RA patients with secondary Sjögren’s syndrome 9.…”
Section: Discussionmentioning
confidence: 99%
“…Animals with defects in regulatory T cells exhibit more severe DED2627. The importance of T cells in human DED is underscored by the efficacy of cyclosporine, a T cell immunosuppressant that is a cornerstone of DED therapy282930. Here, we use impression cytology and flow cytometry to determine the distribution of T RM and recirculating T cell subsets at the ocular surface in healthy humans and in patients with dry eye disease.…”
mentioning
confidence: 99%
“…Dry eye related to immunologic diseases has been described as the most severe form of dry eye. 25 Accordingly, we hypothesize that immunologic alterations of the ocular surface induce the most pronounced corneal nerve fiber damage. However, as this was an observational study, cause and effect (etiology vs. CoS) cannot be differentiated.…”
Section: Cos and Etiology Of Dry Eyementioning
confidence: 99%